ANALISIS KONFLIK SOSIAL DALAM CERPEN “CINTA LELAKI BIASA (Asma Nadia - True Story)” - Gita Widia Pardosi; Achmad Yuhdi (Universitas Palangka Raya, 2023)
A conflict is an argument or disagreement between two or more people. Political conflicts arose from the existence of political power. The essence of political power is society as an object. Conflict is part of social life and arises from personality differences arising from human interactions. The social conflict in this (Asma Nadia - true story) short story